Role of zinc, nitrogen and phosphorus fertilization, and use of microbial inoculation in zinc nutrition of wheat (Triticum aestivum) under different crop establishment methods - SHAHANE, A A; SHIVAY, Y S; KUMAR, D; PRASANNA, R (The Indian Journal of Agricultural Sciences, 2018)
A field experiment was conducted during rabi season of 2013-14 and 2014-15 at the Research Farm of ICAR-Indian Agricultural Research Institute, New Delhi to study the role of N, P and Zn fertilization, and microbial inoculation on concentration and uptake of zinc (Zn) in wheat plant ('HD 2967') at different growth stages, and DTPA-extractable Zn content in soil under three different crop establishment methods (CEMs), viz. conventional drill-sown wheat (CDW), system of wheat intensification (SWI) and zero tillage wheat (ZTW). Experiment was conducted in split-plot design with three CEMs as main plot, viz. CDW, SWI and ZTW. In subplot, two rate of N and P application [100% recommended dose of nutrients (N120P25.8) (RDN) and 75% RDN] and two microbial inoculations (MI), viz. Anabaenasp. (CR1) + Providencia sp. (PR3) (MI1) and Anabaena-Pseudomonas biofilmed formulation (MI2) was applied with 75% RDN making total four combination which were applied with and without Zn (5 kg Zn/ha through zinc sulphate heptahydrate) along with absolute control. Zinc fertilization increased Zn concentration in wheat grain by 3 and 2.9- 3.2 mg/kg when Zn was applied with 100% RDN and 75% RDN + MI1 and 75% RDN + MI2, respectively which showed the role of Zn fertilization in Zn nutrition of wheat. Application of 100% RDN increased total Zn uptake by 78 and 180 g/ha over 75% RDN and control in Zn applied treatments which showed the role of N and P application on Zn nutrition of wheat. Application of MI1 and MI2 with 75% RDN increased grain Zn concentration by 2.3 and2.5 mg/kg indicating their role in Zn nutrition of wheat. Among CEMs, ZTW was found superior and increased Zn concentration in wheat grain by 4.7 and 4.5 mg/kg over CDW and SWI, respectively. Soil DTPA-extractable Zn content was increased in all Zn applied treatments at harvest over initial level which indicates the positive effect of Zn fertilization on soil Zn status. Our study showed that application of recommended dose of Zn alone was not goodÂ  enough to have proper Zn nutrition of wheat and to increase concentration and uptake of Zn in wheat plant and grain, but application of N and P at recommended rate and selecting suitable CEM is equally important.